Technical evaluation and fecal continence of laparoscopic-assisted procedures for total colonic aganglionosis - Chaosheng He; Suolin Li (Elsevier, 2024)
Total colonic aganglionosis (TCA), defined as aganglionosis extending from the anus up to the distal ileum, is a rare variant of Hirschsprung's disease. Surgery for TCA aims to remove the aganglionic colon and reconstruct the intestinal tract by bringing the normally innervated ileum down to the anus while preserving normal sphincter function. Laparoscopy with surgeries including laparoscopic-assisted Duhamel-like and Soave-like pull-through procedures have been progressively applied to the treatment of TCA over the past two decades and may become the dominant treatment for TCA in the future. Postoperative fecal continence, involving issues such as normal defecation, Hirschsprung-associated enterocolitis (HAEC), frequent stool and perianal erosion (perineal rash), soiling/fecal incontinence and constipation/obstructive symptoms, is very important to patients. These complications require nutritional support and comprehensive postoperative gastroenterological care and even require permanent ileostomy and redo pull-through. Some patients have previously seen a psychologist for frequent complaints of diarrhea and other physical symptoms. Patients with TCA postoperatively must be evaluated regularly by pediatric surgeons, enterostoma therapists, gastroenterologists, dieticians and psychologists to achieve a good nutritional status and psychological health.